The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpls.2022.877304
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Factors Involved in Plant Protection-Associated Secondary Metabolite Biosynthesis Pathways

Abstract: Plant specialized metabolites (PSMs) play essential roles in the adaptation to harsh environments and function in plant defense responses. PSMs act as key components of defense-related signaling pathways and trigger the extensive expression of defense-related genes. In addition, PSMs serve as antioxidants, participating in the scavenging of rapidly rising reactive oxygen species, and as chelators, participating in the chelation of toxins under stress conditions. PSMs include nitrogen-containing chemical compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 206 publications
0
23
0
1
Order By: Relevance
“…The taxol biosynthesis pathway is controlled by several environmental and genetic factors (Feng et al., 2023; Yu et al., 2020; Yu et al., 2022; Zhan et al., 2022). Recent studies on taxol biosynthesis regulators mainly focused on stimulus‐responsive TFs (Cao et al., 2022; Chen, Zhang, et al., 2021; Zhang et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The taxol biosynthesis pathway is controlled by several environmental and genetic factors (Feng et al., 2023; Yu et al., 2020; Yu et al., 2022; Zhan et al., 2022). Recent studies on taxol biosynthesis regulators mainly focused on stimulus‐responsive TFs (Cao et al., 2022; Chen, Zhang, et al., 2021; Zhang et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TFs regulated gene expression at the transcriptional level by binding to different cis -acting elements ( Yu et al., 2022a ; Zhan et al., 2022 ; Feng et al., 2023 ). A series of regulatory elements have been identified in the promoter region of TCP genes, including growth-related elements, stress-responsive elements, and hormone signaling-related elements ( Feng et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…IAA auxin is considered a rapid and specific signal that regulates a subset of systemic, JA-dependent secondary metabolites in herbivore-attacked plants. JA-responsive transcription factors were implicated in the production of phenolic acids and alkaloids in various plant species ( Zhan et al, 2022 and references therein). Aphid-infestation induced the biosynthesis and accumulation of alkaloids in lentil accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics engulf compounds containing at least one aromatic ring and one hydroxyl moiety, such as phenolic acids, flavonoids, tannins, etc. ( Zhan et al., 2022 ). Several studies showed that plant secondary compounds have detrimental effects on pea aphids ( Züst & Agrawal, 2016 ).…”
Section: Introductionmentioning
confidence: 99%